Entrepreneurship and poverty reduction; opportunities and challenges. A case study of Lusaka district of Zambia - Martin Chimbala Mwansa (IJEBD (International Journal of Entrepreneurship and Business Development))
The study was prompted by high poverty levels in Lusaka despite several poverty interventions in place. Respondents for the study were drawn from beneficiaries of poverty reduction intervention through stratified random sampling and structured questionnaires where used. Descriptive statistics were employed with results indicating that 97% of respondents categorized themselves as poor. The reason provided for the status quo was inability to generate enough income for normal livelihoods.  An exploration was then done on the role of entrepreneurship with respective challenges and opportunities in increasing incomes and contributing to poverty reduction. Content analysis of literature was done and results highlighted major huddles to entrepreneurship development as access to finance challenges, undeveloped markets, lack of supportive infrastructure and low entrepreneurial competence. This was in the midst of favorable environment supporting the thriving of entrepreneurship.  Recommendations were to remedy identified challenges which if implemented, could lead to thriving entrepreneurship and poverty reduction.